2021
DOI: 10.1136/bmjopen-2021-050569
|View full text |Cite
|
Sign up to set email alerts
|

Use of interrupted time-series analysis to characterise antibiotic prescription fills across pregnancy: a Norwegian nationwide cohort study

Abstract: ObjectivesAntibiotics are the most frequently prescribed medications for pregnant and breastfeeding women. We applied interrupted time-series analysis (ITSA) to describe antibiotic prescription fills patterns in pregnant women and examined recurrent antibiotic fills in subsequent pregnancies.DesignsA population-based drug utilisation study.SettingNorwegian primary care.Participants653 058 pregnancies derived from Medical Birth Registry of Norway linked to the Norwegian Prescription Database (2006–2016).Main ou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 35 publications
5
13
0
Order By: Relevance
“…12 Our findings were consistent with the earlier report from Sweden which found prenatal systemic antibiotic use to be highest during the second trimester, 4 although populationbased studies from Norway and Denmark reported the highest use in the third trimester. 9,12 Antibiotic use during the second trimester peaked between weeks 12 and 13, which corresponds to the timing after the second antenatal visit when infection screening for asymptomatic bacteriuria, UTIs and sexually transmitted infections among others takes place. 33 34,35 The immediate 6 weeks postpartum (puerperium) is especially prone to infections and this was evident in our results, with a proportionately high prevalence of systemic antibiotic use.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…12 Our findings were consistent with the earlier report from Sweden which found prenatal systemic antibiotic use to be highest during the second trimester, 4 although populationbased studies from Norway and Denmark reported the highest use in the third trimester. 9,12 Antibiotic use during the second trimester peaked between weeks 12 and 13, which corresponds to the timing after the second antenatal visit when infection screening for asymptomatic bacteriuria, UTIs and sexually transmitted infections among others takes place. 33 34,35 The immediate 6 weeks postpartum (puerperium) is especially prone to infections and this was evident in our results, with a proportionately high prevalence of systemic antibiotic use.…”
Section: Discussionsupporting
confidence: 92%
“…2006-2016]) 10,12 and our findings could therefore be attributed to relatively higher thresholds for antibiotic prescription in Sweden. 25 Sweden's long-standing national strategic program against antibiotic resistance has overseen sustained reductions in antibiotic use at population level 26 and has invariably been among the lowest in Europe.…”
Section: Discussionmentioning
confidence: 61%
See 2 more Smart Citations
“…Antibiotic exposure was high in this cohort, with 26% of mothers and 42% of children using out-patient antibiotics during pregnancy (including 3 months pre-conception) and first 2 years of life, respectively. However, these figures are comparable to antibiotic consumption in other Nordic countries [ 52 55 ]. Whereas this study cannot determine the underlying pathophysiological mechanisms or establish causality, these results underscore that potential short- and long-term consequences for the mother and child should be considered when prescribing antibiotics during pregnancy and early life.…”
Section: Discussionmentioning
confidence: 52%